Measurement of older adults' performance in digital technology-mediated occupations and management of digital technology. (June 2021) - Fischl, Caroline; Malinowsky, Camilla; Nilsson, Ingeborg
Introduction: Supporting older adults' digital engagement requires an understanding of how occupational performance and technology use are related, as well as having a range of methods that can assist occupational therapists while observing occupational performance and management of technology. The study objectives were to investigate how older adults' ability to perform digital technology-mediated occupations and ability to manage digital technology could be measured and to examine the association between these two abilities. Method: Twenty-five older adults were observed performing digital technology-mediated occupations and managing digital technologies, and were scored on two instruments: the Assessment of Computer-Related Skills and the Management of Everyday Technology Assessment. FACETS was used to generate respective multifaceted Rasch measurement models for scores on the instruments. The Spearman correlation test was used to investigate correlation between person ability measures from respective Rasch models of the instruments. Results: The results include item, occupation, and technology difficulty estimates, as well as person ability measures that could illustrate older adults' ability to perform occupations and to manage technology. There is also a strong positive correlation between these abilities. Conclusion: Insight into an older person's ability to manage technology can provide information about his or her ability to perform digital technology-mediated occupations and vice versa.